High-performance powder metallurgy process
By adding a specific proportion of copper powder, carbon fiber particles, graphite and paraffin to iron-based powder metallurgy parts, and using powder metallurgy technology for sintering and post-treatment, the problem of insufficient strength and wear resistance of iron-based powder metallurgy parts is solved, and the effect of high hardness, strength and wear resistance is achieved.
Patent Information
- Application Number
- CN202411811710.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Iron-based powder metallurgical parts generally have problems in the automobile industry that are not strong enough and have poor wear resistance, which cannot meet the high performance requirements of automotive parts.
A specific proportion of copper powder, carbon fiber particles, graphite and paraffin are mixed with iron powder, and sintered and post-treated through powder metallurgy processes to form an iron-based powder metallurgy part with high hardness, strength and wear resistance.
On the basis of maintaining a low cost, the strength, wear resistance and density of iron-based powder metallurgical parts are improved, meeting the high performance requirements of automotive parts.
Smart Images

Figure BDA0005180707300000071 
Figure BDA0005180707300000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of powder metallurgy, and in particular to a high-performance powder metallurgy process. Background Art
[0002] Powder metallurgy is a powder sintering technology that uses metal powder or a mixture of metal powder and non-metal powder as raw materials, and then forms and sinters them to manufacture metal materials, composite materials, and various types of products. Powder metallurgy can directly produce porous, semi-dense or fully dense materials and products. It is a process with little or no cutting and is widely used in transportation, machinery, electronics, aerospace, new energy and other fields.
[0003] As the most commonly used material in powder metallurgy, iron-based powder metallurgy has low production cost and good performance, and is widely used. Iron-based powder metallurgy uses iron powder as raw material, and may also add trace amounts of other metal powders, non-metallic powders and lubricant powders. Iron-based powder metallurgy parts are widely used in the automotive industry.
[0004] With the development of the automotive industry, the performance requirements for iron-based powder metallurgy parts are getting higher and higher, but iron-based powder metallurgy parts generally have the disadvantages of insufficient strength and poor wear resistance, which cannot meet the requirements of automotive parts. Therefore, it is necessary to improve the formula and process of iron-based powder metallurgy to improve the hardness, strength and wear resistance of iron-based powder metallurgy parts. Summary of the invention
[0005] In order to improve the hardness, strength and wear resistance of iron-based powder metallurgy parts, the present application provides a high-performance powder metallurgy process.
[0006] A high-performance powder metallurgy process provided in this application adopts the following technical solution: A high performance powder metallurgy process comprising the following steps: Mixing: Evenly mix iron powder, copper powder, carbon fiber particles, graphite, and paraffin in a weight ratio of 97%-98%: 0.7%-1.3%: 0.1%-0.3%: 0.3%-0.5%: 0.7%-1.1% to obtain iron-based powder; Pressing: Put the mixed iron-based powder into the press, and the press will send the iron-based powder into the forming mold, and then press it into a green embryo through the mold; Sintering: Put the green embryo into the sintering furnace and sinter it until it cools to room temperature to form a semi-finished product; Post-processing: The semi-finished parts are post-processed by finishing, oil immersion, machining, heat treatment or electroplating to obtain finished powder metallurgy parts.
[0007] By adopting the above technical scheme, copper powder, carbon fiber particles, graphite and paraffin are added in specific proportions to the raw materials of iron-based powder. The prepared powder metallurgy parts have excellent strength and wear resistance while maintaining low cost, and the hardness and density of the parts are improved and the density is enhanced.
[0008] Copper powder can fill the gaps between iron powder particles, reduce porosity, and improve the density and hardness of the sample after sintering. At the same time, the addition of copper powder can promote the connection and diffusion of the particle interface, form a copper phase interface during sintering, and improve strength. Carbon fiber particles and graphite are both used as carbon sources. Carbon fiber particles have higher activity and can be oxidized more violently during sintering. Both carbon fiber particles and graphite powder can diffuse into the iron matrix to promote sintering and hardening. At the same time, carbon fiber particles can reduce the oxide film on the surface of the particles, promote the shrinkage and densification of the sintered body, and improve strength, toughness and corrosion resistance. Part of the graphite powder can remain in the gap as a solid lubricant to improve friction performance, fatigue resistance and wear resistance. Paraffin wax replaces zinc stearate as a lubricant, which can improve the density, hardness and finish of powder metallurgy parts while being harmless to the environment.
[0009] In a preferred embodiment, the carbon fiber particles are prepared by the following steps: The polyacrylonitrile-based chopped carbon fibers are placed in acetone and ultrasonically dispersed and cleaned for 40-50 minutes to obtain degummed chopped carbon fibers; The degummed chopped carbon fibers are ball-milled at a rotation speed of 200 r / min for 5-5.5 hours, and the carbon fiber particles with a particle size of 1-4 μm are sieved.
[0010] By adopting the above technical scheme, the polyacrylonitrile-based chopped carbon fibers are degummed by acetone washing, and the length of the carbon fibers is shortened by ball milling to obtain carbon fiber particles that can be evenly dispersed in an iron matrix. After the ball milling treatment, the specific surface area of the carbon fiber particles is increased and the activity is improved.
[0011] In a preferred embodiment, the iron-based powder in the mixing step includes, by weight, 98% iron powder, 0.8% copper powder, 0.1% carbon fiber particles, 0.3% graphite, and 0.8% paraffin.
[0012] By adopting the above technical solution, the powder metallurgy parts formed by sintering the iron-based powders in the above specific proportions have the best comprehensive performance.
[0013] In a preferred embodiment, the graphite is modified graphite, and the modified graphite is prepared by the following steps: Mix phenolic resin and anhydrous ethanol, and heat to 60-65°C to prepare a saturated phenolic resin ethanol solution; The flake graphite is soaked in a saturated phenolic resin ethanol solution for 30-40 minutes, wherein the mass ratio of the flake graphite to the phenolic resin is 1:(0.08-0.2), and then taken out and dried in an oven at 80-90°C until the mass no longer changes, thereby obtaining modified graphite.
[0014] By adopting the above technical scheme, phenolic resin is used to coat the surface of flake graphite, which promotes the uniform dispersion of modified graphite in the iron matrix, reduces the local adsorption and agglomeration of graphite powder, protects the structural integrity of graphite during mixing and pressing, and helps to enhance the performance of graphite on sintered bodies.
[0015] In a preferred embodiment, the iron powder is selected from one or more of reduced iron powder, water atomized iron powder, and carbonyl iron powder.
[0016] In a preferred embodiment, the iron powder is a mixture of water-atomized iron powder and reduced iron powder, wherein the reduced iron powder accounts for 80%-85% of the weight of the mixture, the mesh size of the reduced iron powder is -150 mesh, and the water-atomized iron powder accounts for 15%-20% of the weight of the mixture, and the mesh size of the water-atomized iron powder is -400 mesh.
[0017] By adopting the above technical solution, through the combination of iron powders of different particle sizes and types, the shape of the water-atomized iron powder is regular and not segregated, and the internal pores of the reduced iron powder can be filled, while the loose density of the iron matrix is increased and the sintering performance is enhanced.
[0018] In a preferred embodiment, the copper powder is electrolytic copper powder, and the particle size of the copper powder is -200 mesh.
[0019] By adopting the above technical solution, electrolytic copper powder with smaller particle size is selected, which has a good synergistic effect with carbon fiber particles and graphite, and jointly enhances the strength and density of the sintered body.
[0020] In a preferred embodiment, the specific operation in the mixing step is to mix in a mixer at a rotation speed of 30-40 r / min for 60-80 min, and pass through an 80-mesh sieve to obtain the iron-based powder.
[0021] By adopting the above technical solution, the rotation speed and mixing time are limited, so that the carbon fiber particles and graphite can be evenly dispersed in the iron matrix while keeping the structure intact and not destroyed.
[0022] In a preferred embodiment, the pressure in the pressing step is controlled at 560-630 MPa.
[0023] By adopting the above technical solution, the molding pressure is controlled to obtain a complete green embryo.
[0024] In a preferred embodiment, in the sintering step, the protective atmosphere is nitrogen and hydrogen, and electric heating is used for preheating, the preheating temperature is 600-800°C, the sintering temperature is 1050-1120°C, and the sintering time is 3-4.5h.
[0025] By adopting the above technical solution, the sintering temperature is controlled so that the raw material components react fully to obtain a sintered body with high hardness, high strength and high wear resistance.
[0026] In summary, the present application has at least one of the following beneficial effects: 1. By adding copper powder, carbon fiber particles, graphite and paraffin in a specific proportion to the raw materials of iron-based powder, the prepared powder metallurgy parts have excellent strength and wear resistance while maintaining a low cost. The hardness and density of the parts are improved, and the density is enhanced.
[0027] Copper powder can fill the gaps between iron powder particles, reduce porosity, and improve the density and hardness of the sample after sintering. At the same time, the addition of copper powder can promote the connection and diffusion of the particle interface, form a copper phase interface during sintering, and improve strength. Carbon fiber particles and graphite are both used as carbon sources. Carbon fiber particles have higher activity and can be oxidized more violently during sintering. Both carbon fiber particles and graphite powder can diffuse into the iron matrix to promote sintering and hardening. At the same time, carbon fiber particles can reduce the oxide film on the surface of the particles, promote the shrinkage and densification of the sintered body, and improve strength, toughness and corrosion resistance. Part of the graphite powder can remain in the gap as a solid lubricant to improve friction performance, fatigue resistance and wear resistance. Paraffin wax replaces zinc stearate as a lubricant, which can improve the density, hardness and finish of powder metallurgy parts while being harmless to the environment.
[0028] 2. Use phenolic resin to coat the surface of flake graphite to promote the uniform dispersion of modified graphite in the iron matrix, reduce the local adsorption and agglomeration of graphite powder, protect the structural integrity of graphite during mixing and pressing, and help graphite enhance the performance of sintered bodies. DETAILED DESCRIPTION
[0029] The present application is further described in detail below in conjunction with Examples 1-8 and Comparative Examples 1-2.
[0030] Preparation Example Preparation Example 1 Preparation of carbon fiber particles The polyacrylonitrile-based chopped carbon fibers are placed in acetone and subjected to ultrasonic dispersion cleaning for 40 minutes for degumming treatment to obtain degummed chopped carbon fibers; The degummed chopped carbon fiber is ball milled with a ball mill, the mass ratio of stainless steel grinding balls to powder is 5:1, the diameter of the grinding balls is 3-10 mm, the ball milling is carried out at a rotation speed of 200 r / min for 5 hours, and the carbon fiber particles with a particle size of 1-4 μm are obtained by sieving.
[0031] Preparation Example 2 Preparation of carbon fiber particles The polyacrylonitrile-based chopped carbon fibers are placed in acetone and subjected to ultrasonic dispersion cleaning for 50 minutes for degumming treatment to obtain degummed chopped carbon fibers; The degummed chopped carbon fiber is ball-milled in a ball mill with a mass ratio of stainless steel grinding balls to powder of 5:1 and a grinding ball diameter of 3-10 mm. The ball milling is performed at a rotation speed of 200 r / min for 5.5 h, and carbon fiber particles with a particle size of 1-4 μm are obtained by sieving.
[0032] Preparation Example 3 Preparation of modified graphite The phenolic resin and anhydrous ethanol are mixed and heated to 60°C to prepare a saturated phenolic resin ethanol solution; The flake graphite was immersed in a saturated phenolic resin ethanol solution for 30 minutes, wherein the mass ratio of the flake graphite to the phenolic resin was 1:0.08. After being fished out, it was dried in an oven at 80°C until the mass no longer changed, thereby obtaining modified graphite.
[0033] Preparation Example 4 Preparation of modified graphite The phenolic resin and anhydrous ethanol are mixed and heated to 65°C to prepare a saturated phenolic resin ethanol solution; The flake graphite was immersed in a saturated phenolic resin ethanol solution for 40 minutes, wherein the mass ratio of the flake graphite to the phenolic resin was 1:0.2. After being fished out, it was dried in an oven at 90°C until the mass no longer changed, thereby obtaining modified graphite. Example
[0034] Example 1 A high performance powder metallurgy process The iron-based powders used in high-performance powder metallurgy materials include: Iron powder 97%, using reduced iron powder with an average particle size of -100 mesh; Copper powder 1.2%, using electrolytic copper powder with an average particle size of -200; 0.3% carbon fiber particles, using the carbon fiber particles prepared in Preparation Example 1; Graphite 0.5%; Paraffin 1%.
[0035] The high performance powder metallurgy process includes the following steps: Mixing: put iron powder, copper powder, carbon fiber particles, graphite and paraffin into a mixer, mix at a speed of 30r / min for 60min, mix evenly and pass through an 80-mesh sieve to obtain iron-based powder; Pressing: Put the mixed iron-based powder into the press, which feeds the iron-based powder into the forming die, controls the pressure at 560MPa, and presses it into a green embryo through the die; Sintering: Place the green embryo on the conveyor mesh belt, and then put it into the mesh belt sintering furnace for sintering. The protective atmosphere is nitrogen and hydrogen. During the sintering process, it is first preheated with electric heating. The preheating temperature is 600℃, the sintering temperature is 1050℃, and the sintering time is 3h. Then it is cooled to room temperature to form a semi-finished product. Post-processing: The semi-finished parts are post-processed by finishing, oil immersion, machining, heat treatment or electroplating to obtain finished powder metallurgy parts.
[0036] Example 2 A high performance powder metallurgy process The iron-based powders used in high-performance powder metallurgy materials include: Iron powder 98%, water atomized iron powder with an average particle size of -200 mesh; Copper powder 0.7%, using electrolytic copper powder with an average particle size of -200; 0.3% carbon fiber particles, using the carbon fiber particles prepared in Preparation Example 1; Graphite 0.3%; Paraffin 0.7%.
[0037] The high performance powder metallurgy process includes the following steps: Mixing: put iron powder, copper powder, carbon fiber particles, graphite and paraffin into a mixer, mix at a speed of 40r / min for 80min, mix evenly and pass through an 80-mesh sieve to obtain iron-based powder; Pressing: Put the mixed iron-based powder into the press, which feeds the iron-based powder into the forming die, controls the pressure at 630MPa, and presses it into a green embryo through the die; Sintering: Place the green embryo on the conveyor mesh belt, and then put it into the mesh belt sintering furnace for sintering. The protective atmosphere is nitrogen and hydrogen. During the sintering process, it is first preheated with electric heating. The preheating temperature is 800℃, the sintering temperature is 1120℃, and the sintering time is 4.5h. Then it is cooled to room temperature to form a semi-finished product. Post-processing: The semi-finished parts are post-processed by finishing, oil immersion, machining, heat treatment or electroplating to obtain finished powder metallurgy parts.
[0038] Example 3 A high performance powder metallurgy process The iron-based powders used in high-performance powder metallurgy materials include: Iron powder 98%, using reduced iron powder with an average particle size of -150 mesh; Copper powder 0.8%, using electrolytic copper powder with an average particle size of -200; 0.1% carbon fiber particles, using the carbon fiber particles prepared in Preparation Example 2; Graphite 0.3%; Paraffin 0.8%.
[0039] The high performance powder metallurgy process includes the following steps: Mixing: put iron powder, copper powder, carbon fiber particles, graphite and paraffin into a mixer, mix at a speed of 35r / min for 70min, mix evenly and pass through an 80-mesh sieve to obtain iron-based powder; Pressing: Put the mixed iron-based powder into the press, which feeds the iron-based powder into the forming die, controls the pressure at 590MPa, and presses it into a green embryo through the die; Sintering: Place the green embryo on the conveyor mesh belt, and then put it into the mesh belt sintering furnace for sintering. The protective atmosphere is nitrogen and hydrogen. During the sintering process, it is first preheated with electric heating. The preheating temperature is 700℃, the sintering temperature is 1080℃, and the sintering time is 4h. Then it is cooled to room temperature to form a semi-finished product. Post-processing: The semi-finished parts are post-processed by finishing, oil immersion, machining, heat treatment or electroplating to obtain finished powder metallurgy parts.
[0040] Example 4 The difference between this embodiment and embodiment 3 is that the iron powder in the iron-based powder raw material is different.
[0041] The iron powder of this embodiment is a mixture of water-atomized iron powder and reduced iron powder, wherein the reduced iron powder accounts for 80% and has a mesh size of -150 mesh; the water-atomized iron powder accounts for 20% and has a mesh size of -400 mesh.
[0042] The powder metallurgy process of this embodiment is the same as that of embodiment 3.
[0043] Example 5 The difference between this embodiment and embodiment 3 is that the iron powder in the iron-based powder raw material is different.
[0044] The iron powder of this embodiment is a mixture of water-atomized iron powder and reduced iron powder, wherein the reduced iron powder accounts for 85% and has a mesh size of -150 mesh; the water-atomized iron powder accounts for 15% and has a mesh size of -400 mesh.
[0045] The powder metallurgy process of this embodiment is the same as that of embodiment 3.
[0046] Example 6 The difference between this embodiment and embodiment 3 is that the graphite in the iron-based powder raw material is different.
[0047] The graphite of this embodiment is the modified graphite obtained in Preparation Example 3.
[0048] The powder metallurgy process of this embodiment is the same as that of embodiment 3.
[0049] Example 7 The difference between this embodiment and embodiment 3 is that the graphite in the iron-based powder raw material is different.
[0050] The graphite of this embodiment is the modified graphite obtained in Preparation Example 4.
[0051] The powder metallurgy process of this embodiment is the same as that of embodiment 3.
[0052] Example 8 The difference between this embodiment and embodiment 3 is that the iron powder and graphite in the iron-based powder raw material are different.
[0053] The iron powder of this embodiment is a mixture of water-atomized iron powder and reduced iron powder, wherein the reduced iron powder accounts for 85% and has a mesh size of -150 mesh; the water-atomized iron powder accounts for 15% and has a mesh size of -400 mesh; the graphite is the modified graphite obtained in Preparation Example 4.
[0054] The powder metallurgy process of this embodiment is the same as that of embodiment 3.
[0055] Comparative Example Comparative Example 1 The difference between this comparative example and comparative example 1 is that an equal weight of graphite is used in the iron-based powder raw material to replace the carbon fiber particles.
[0056] The powder metallurgy process of this embodiment is the same as that of embodiment 1.
[0057] Comparative Example 2 The difference between this comparative example and comparative example 1 is that an equal weight of zinc stearate is used to replace graphite in the iron-based powder raw material.
[0058] The powder metallurgy process of this embodiment is the same as that of embodiment 1.
[0059] Performance Testing The powder metallurgy parts prepared in Examples 1-8 and Comparative Examples 1-2 were subjected to the following performance tests: Density: The density of powder metallurgy parts is tested using the Archimedes drainage method.
[0060] Hardness: The hardness of powder metallurgy parts is tested according to the method in GB / T 230.1-2009 "Rockwell hardness test for metallic materials".
[0061] Tensile strength: The tensile strength of powder metallurgy parts is tested according to the method in GB / T 19076-2022 "Specification for Sintered Metal Materials".
[0062] Data Analysis: According to the above table, the present application uses iron-based powder raw materials of specific components, uses carbon fiber particles and graphite as carbon sources to react with iron powder and copper powder, and uses paraffin as a lubricant. The powder metallurgy parts obtained by sintering have good density and hardness, excellent mechanical properties, and the parts have good corrosion resistance and wear resistance.
[0063] After the graphite is coated and modified with phenolic resin, the agglomeration and adsorption of the modified graphite are reduced, which promotes the dispersion and compatibility of the modified graphite in the iron matrix, thereby strengthening the C-Cu and C-Fe reactions, allowing the graphite to fully exert its hardening and strengthening effects on the sintered body, and further improving the performance of powder metallurgy parts.
[0064] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high performance powder metallurgy process, characterized in that: The following steps are involved: Mixing: Evenly mix iron powder, copper powder, carbon fiber particles, graphite, and paraffin in a weight ratio of 97%-98%: 0.7%-1.3%: 0.1%-0.3%: 0.3%-0.5%: 0.7%-1.1% to obtain iron-based powder; Pressing: The mixed iron-based powder is put into a press, which feeds the iron-based powder into a forming die and presses it into a green embryo through the die; Sintering: Place the green body into a sintering furnace and sinter it until it cools to room temperature to form a semi-finished product. Post-processing: The semi-finished parts are post-processed by finishing, oil immersion, machining, heat treatment or electroplating to obtain finished powder metallurgy parts.
2. A high performance powder metallurgy process according to claim 1, characterized in that: The carbon fiber particles are prepared by the following steps: The polyacrylonitrile-based chopped carbon fibers are placed in acetone and ultrasonically dispersed and cleaned for 40-50 minutes to obtain degummed chopped carbon fibers; The degummed chopped carbon fibers are ball-milled at a rotation speed of 200 r / min for 5-5.5 hours, and the carbon fiber particles with a particle size of 1-4 μm are sieved.
3. A high performance powder metallurgy process according to claim 1, characterized in that: In the mixing step, the iron-based powder comprises, by weight, 98% iron powder, 0.8% copper powder, 0.1% carbon fiber particles, 0.3% graphite, and 0.8% paraffin.
4. A high performance powder metallurgy process according to claim 1, characterized in that: The graphite is modified graphite, and the modified graphite is prepared by the following steps: Mix phenolic resin and anhydrous ethanol, and heat to 60-65°C to prepare a saturated phenolic resin ethanol solution; The flake graphite is soaked in a saturated phenolic resin ethanol solution for 30-40 minutes, wherein the mass ratio of the flake graphite to the phenolic resin is 1:(0.08-0.2), and then taken out and dried in an oven at 80-90°C until the mass no longer changes, thereby obtaining modified graphite.
5. A high performance powder metallurgy process according to claim 1, characterized in that: The iron powder is selected from one or more of reduced iron powder, water atomized iron powder and carbonyl iron powder.
6. A high performance powder metallurgy process according to claim 5, characterized in that: The iron powder is a mixture of water-atomized iron powder and reduced iron powder, wherein the reduced iron powder accounts for 80%-85% of the weight of the mixture, the mesh size of the reduced iron powder is -150 mesh, and the water-atomized iron powder accounts for 15%-20% of the weight of the mixture, the mesh size of the water-atomized iron powder is -400 mesh.
7. A high performance powder metallurgy process according to claim 1, characterized in that: The copper powder is electrolytic copper powder, and the particle size of the copper powder is -200 mesh.
8. A high performance powder metallurgy process according to claim 1, characterized in that: The specific operation in the mixing step is to mix in a mixer at a rotation speed of 30-40 r / min for 60-80 min, and pass through an 80-mesh sieve to obtain an iron-based powder.
9. A high performance powder metallurgy process according to claim 1, characterized in that: The pressure in the pressing step is controlled at 560-630 MPa.
10. A high performance powder metallurgy process according to claim 1, characterized in that: In the sintering step, the protective atmosphere is nitrogen and hydrogen, and electric heating is used for preheating at a preheating temperature of 600-800° C., the sintering temperature is 1050-1120° C., and the sintering time is 3-4.5 hours.
Citation Information
Patent Citations
Powder metallurgy prescription and technique
CN101249562A
Short carbon fiber modified high friction composite and preparing method and application thereof
CN108018506A
Preparation method for carbon particle reinforced metal base composite materials
CN109518032A
Preparation method of metal material or metal composite material
CN109852831A
Sintered bearing
JP2017161072A